Performance and Scalability Analysis of Node.js and PHP/Nginx Web Application - Yoseph Pandji D.; Willy Sudiarto Raharjo (Jurnal Informatika, 2014)
Node.js is an application framework that can be used to build network server and web application. Due to its maturity, Node.js should be tested in various aspects such as performance and scalability to build dynamic web application. For comparison, we use PHP/Nginx web development stack to build web application to compare and analyze Node.js web application performance and scalability. For research purpose, we build dummy applications based on Dijkstra Algorithm to calculate shortest path between nodes, in this case Trans Jogja shelters. Using load generator, we simulate concurrent user requests to test performance and scalability of Node.js and PHP/Nginx web application. The general results of this research showed that Node.js application had higher performance and scalability than PHP/Nginx application.